MAGNETIC FIELD-DEPENDENT ELECTRIC CURRENT ON A PERIODIC POLY(DA)-POLY(DT) DNA MOLECULE STRUCTURE - Efta Yudiarsah (Program Studi Fisika Universitas Negeri Jakarta, 2022)
An electric current flowing on the Poly(dA)-poly(dT) DNA molecule structure has been calculated. The current was calculated from transmission probabilities by employing Landauer-Buttiker formalism. Green’s function technique has been used for obtaining the transmission probabilities. The DNA molecule structure was modeled within the tight-binding Hamiltonian model approach. The model takes into account electron hopping parameters which are dependent on the magnetic field as well as the electric field. The presence of a magnetic field causes the Peierls phase factor on the electron hopping parameters. The calculation results at low electric voltages show that after decreasing, the electric current oscillates with the magnetic field. However, at higher electric voltages, the electric current is increasing and oscillates with the magnetic field.